Canadian contexts for exploring transformative student agency through place-conscious pedagogy - Kelly, Darron; Pelech, Sharon (University of Aberdeen, 2020)
Open access article. Creative Commons Attribution-NonCommercial 4.0 International license (CC BY-NC 4.0 DEED) applies Findings are presented from two case studies of student agency in relation to place-conscious pedagogy in the Canadian provinces of Alberta and Newfoundland and Labrador. For the purpose of these studies, student agency is viewed as transformative and encompasses self-determination, successful attainment of personal objectives, and enhanced willingness to address societal issues (Biesta & Tedder, 2007; Goodman & Eren, 2013). Place-conscious pedagogy uses the local community and environment as focal points for teaching and learning (Greenwood, 2013; Gruenewald, 2003; Lescure & Yaman, 2014; Kelly, 2007, 2013, 2014; Pelech & Kelly, 2017; Smith, 2007; Sobel, 2005). The underlying premise for exploring student agency in relation to place-conscious pedagogy is that students who actively participate in understanding and shaping the world around them learn to recognize their potential as agents of personal and social transformation (Kelly & Pelech, in press). Each case study is guided by two interrelated questions: what practices do place-conscious teachers offer students; and how do these teachers understand the relationship of such practices to student agency? Semi-structured interviews with classroom teachers and photographic documentation of teaching practices are used to address these questions. Our research supports ministries of education, school divisions, teacher education programs, and classroom teachers in moving forward with innovative and transformative curriculum redesign (Government of Alberta, 2017; Government of Newfoundland and Labrador, 2017). This research also contributes to development of more culturally and environmentally aware and engaged youth by recognizing, documenting, and supporting tangible commitments to the educational value of place and local awareness (Webber & Miller, 2016). Yes